Comparison of the Biochemical Composition and Nutritional Quality Between Diploid and Triploid Hong Kong Oysters, Crassostrea hongkongensis - Qin, Yanping; Zhang, Yuehuan; Ma, Haitao; Wu, Xiangwei; Xiao, Shu; Li, Jun; Mo, Riguan; Yu, Ziniu (Frontiers in Physiology, 2018)
This study is the first systematic comparison of the biochemical composition and nutritional quality between diploid and triploid Hong Kong oysters, Crassostrea hongkongensis. Results showed that in the reproductive season, the glycogen content in five tissues (gill, mantle, adductor muscle, labial palps and gonad) was significantly higher (P < 0.05) in triploids than in diploids, with odds ratios (ORs) of 96.26%, 60.17%, 72.59%, 53.56% and 128.52%, respectively. In the non-reproductive phase significant differences in glycogen content (P < 0.05) between diploid and triploid oysters existed only in gill and gonad. In both diploid and triploid Hong Kong oysters, quantitative real-time PCR analysis of the glycogen synthesis gene (ChGS) and glycogen phosphorylase gene (ChGP) showed that the gene expression patterns matched the pattern of variation in glycogen content. Moreover, in both the reproductive and the non-reproductive phases, triploid Hong Kong oysters had a well balance of essential amino acids and were thus a well source of high-quality protein. Surprisingly, in both phases, significantly higher (P < 0.05) percentages of four essential fatty acids (α-linolenic acid, linoleic acid, eicosapentaenoic acid and docosahexaenoic acid) were observed in triploids than in diploids. Additionally, the ratio of n-3/n-6 polyunsaturated fatty acids (PUFAs) was much higher in triploids than that in diploids. Variations in Biochemical composition were consistent with the relative expression of the citrate synthase gene (ChCS) and the α-ketoglutarate dehydrogenase gene (ChKD), which are key enzyme genes of the tricarboxylic acid cycle. Overall, the triploid Hong Kong oyster has a better nutritional value and taste than the diploid in terms of glycogen content, protein quality and fatty acid content.